A STUDY ON THE FACTORS INFLUENCING YOUNG MUSLIMS’ BEHAVIORAL INTENTION IN CONSUMING HALAL FOOD IN MALAYSIA - Abdul Khalek, Aiedah; Syed Ismail, Sharifah Hayaati; Mohamad Ibrahim, Hairunnisa (Jurnal Syariah, 2017)
This study aims to identify the factors that influence young Muslims’ behavioral intention to consume halal food in the Malaysian Private Higher Learning Institutions. Ajzen’s Theory of Planned Behavior (TPB), adapted as a theoretical framework postulates three components which are attitude, subjective norms and behavioral control of consumers. Data were collected through self-administered questionnaires using a 5 point Likert Scale. The respondents are young Malaysian Muslim consumers between the ages of 16 and 35 years. The findings of this study show the intention to consume halal food in Klang Valley, Malaysia is predominantly influenced by young Muslims’ positive attitudes and their behavioral control towards halal food. The factor of subjective norms is found to have no significant influence as compared to the attitude and behavioral control of young Muslims’ behavioral intention in consuming halal food in Malaysia. The respondents were from higher learning institutions in Klang Valley. Therefore, future research may broaden the sample size and expand the geographical areas to other states in Malaysia. Future research also may look into the influence of behavioral control and subjective norms towards the attitude of young consumers in choosing halal food and other products. This study contributes and extends knowledge of the Muslim consumers’ behaviors in consuming halal food. The findings provide information to the manufacturers in expanding their market and for governmental agencies and associations to promote halal food consumption.